DETERMINANT THE CAUSES OF EMPLOYEE TURNOVER - Pongoh, Rio A.J. (Universitas Sam Ratulangi, 2013)
One of the most common problem faces in Indonesia is unemployed. This problem is followed by lack of work field. So the people do not have other options, instead looking for any opportunity jobs. Sometimes, the jobs that accepted by individuals and later will become new employees in a company are not as equal as they expected. This creates the employees to turnover, which causing the companies to loss workers and pay the costs. The objective of this research is to find out the causes of employee turnover. This research will use saturated sampling method were all the numbers of population are taken as a sample, and confirmatory factor analysis to analyze identified factors. Questionnaires are taken to collect data. Twenty one factors are manage to identified, but only eighteen are affect the causes of employee turnover, and those eighteen factors create five new factors. The first factor is job stress, the second is morale motivation, the third is emotions management, the fourth is job engagement, and the fifth is employee-organization relationship. There are also three variables that do not affect the employee turnover, which are bullying and harassment, job workload, and performance appraisal. Keywords: employee turnover